Effect of amino acid administration on generative growth and brix value of sugarcane plant (Saccharum officinarum L.) Bululawang varieties - Irma Wardati; Muhammad Fadrul Afandi; Abdurrahman Salim; Nisa Budi Arifiana; Ferril Muhammad Nur; Ni Nengah Putri Adnyani; Cinantya Anindita, Devina (International Integrated Agricultural Journal (IIAJ), 2025)
Sugarcane (Saccharum officinarum L.) is a strategic crop that is the primary raw material for sugar and has an important role in the economy. Domestic sugar production has not met national needs due to various constraints, such as low yield, poor seed quality, and soil damage due to inorganic fertilizers. The application of amino acids as organic fertilizers can potentially increase sugarcane productivity by improving plant metabolism and soil microbial activity. This study aimed to determine the effect of amino acid administration on generative growth and the Brix value of sugarcane plants (Saccharum officinarum L.). Varieties of sea lining. The research was implemented from February to June 2024 at the Lapang Laboratory, Department of Agricultural Production, Politeknik Negeri Jember. The method used in the study is the Group Random Design (RAK) method, which involves 1 factor, namely, Amino Acid organic fertilizer has four levels of amino acid dosage, namely A0 = Control (without amino acid administration), A1 = Amino Acid 250 ml/polybag, A2 = Amino Acid 500 ml/polybag and A3 = Amino Acid 750 ml/polybag. The data obtained from the research results was analyzed using ANOVA and then further tested using BNJ at the level of 5%. The results of the study found that the application of amino acids to sugarcane plants (Saccharum officinarum L.) had a real effect on the height of the plant at 188 HST, the stem diameter of 218 and 249 HST, and very real on the stem diameter of 188 HST and the root volume of 249 HST. However, the effect was not significant on the plant height of 218 HST, 249 HST, and Brix values.